(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2026)
This study aims to analyze entrepreneurial readiness of vocational school students in Surabaya by examining the role of Teaching Factory and entrepreneurial intention, with entrepreneurial mindset positioned as a mediating variable, in order to address gaps in existing vocational entrepreneurship literature. Teaching Factory is an industry-based learning model that emphasizes hands-on practice, involvement with the business world, and the development of entrepreneurial skills. This research uses the Literature Review approach with descriptive methods. The results showed that Teaching Factory has a positive and significant effect on entrepreneurial readiness, both directly and through the mediation of an entrepreneurial mindset. Entrepreneurial intention is also proven to have a significant influence on the readiness of graduates to start a business independently. In addition, an entrepreneurial mindset acts as a mediator that strengthens the relationship between practical learning experiences and real readiness to face the business world. This study recommends strengthening the implementation of the teaching factory program as training to develop entrepreneurial mindset systematically in the SMK curriculum